The Effects Of Fan Activity And Views On Purchase Decision In The Genshin Impact Fanwork Market: a Literature Synthesis - Nathania, Gabriella Callista Firsty; Aprilianty, Fitri (Journal of Consumer Studies and Applied Marketing, 2023)
Since the beginning of the industry, role-playing games (RPGs) have been among the most widely played game categories. As one of the worldwide top-grossing role-playing games in 2022, Genshin Impact is currently the 4th most popular game In Indonesia. With this popularity, many commercialized Genshin Impact fanworks circulated daily in the fan community, more popularly known as fandom. However, not all fanworks are accepted in the fandom and are considered "problematic works." Therefore, this research aims to know what factors support the purchase decision of Genshin Impact fanworks in Indonesia and the impact of negative factors of Genshin Impact fanworks on the purchase decision of Indonesian Genshin Impact fans. The findings of this study are expected to be of help to Genshin Impact fan workers in Indonesia.